2016
DOI: 10.1080/09540253.2016.1263290
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a woman doctor in Iran: the formation of classed and gendered selves

Abstract: This paper analyses the pedagogical pathways of a group of first--generation Iranian migrant doctors in the UK. It explores the complex system of class production and growing up as a classed subject in Iran, a process that ties young women's educational aspirations to female independence on the one hand and to the modern feminine, heterosexual identity that sees women as part of the patriarchal family system on the other. By using Bourdieu's concept of cultural capital and habitus (Bourdieu 1984) and Foucault'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…This also includes communication about different life issues, such as discussions about education and professions (Table 1, quote A1), encouragement (Table 1, quote A10), and what they can achieve, such as becoming a doctor (Table 1, quote A6), in their personal life. Fathi (2018) pointed out that research has shown that parental involvement in raising children has an impact on their educational achievement, career path, and educational aspirations. In this process with the parents, however, the children and adolescents are often also actors in the migration process.…”
Section: Category One: Family Valuesmentioning
confidence: 99%
“…This also includes communication about different life issues, such as discussions about education and professions (Table 1, quote A1), encouragement (Table 1, quote A10), and what they can achieve, such as becoming a doctor (Table 1, quote A6), in their personal life. Fathi (2018) pointed out that research has shown that parental involvement in raising children has an impact on their educational achievement, career path, and educational aspirations. In this process with the parents, however, the children and adolescents are often also actors in the migration process.…”
Section: Category One: Family Valuesmentioning
confidence: 99%
“…Burada ailenin rollerinden birisi de sadece yasal kazanç ve dağılıma bağlı bir ekonomik faaliyetten çok; helal, temiz, paylaşıma dayalı ve yeteri kadar kazanç esaslı bir motivasyonu örgütlenmiş olmasıydı. İddia edildiği gibi belirgin ekonomik sınıf farkından (Fathi, 2018) bahsetmek mümkün değildi. Zira medeniyetimizde insanın kıymetini belirleyen şey onun sahip olduğu ya da mahrum olduğu makam ve mülkiyet değil, sahip olduklarına nasıl temas ettiği, sahip olmadıklarını nasıl karşıladığıyla ilgili, inanç, tutum, davranış ve pratikleriydi.…”
Section: üRetim-tüketim Döngüsü Ve Aileunclassified
“…Higher education is predominantly controlled by men, with women playing a negligible part (Sedghi, 2007); however, quite interestingly, girls currently account for a larger number of Iranian university students. Neither the population of female university students nor mixed university education is desirable to the cultural policies of the Islamic Republic of Iran, as women are expected to spend most of their time at home taking care of their families (Fathi, 2016). Therefore, the large number of female students at Iranian universities is by no means an indication of Iranian women's success in attaining scientific positions and entering the labor market (Rezaei, 2012).…”
Section: Introductionmentioning
confidence: 99%